Systematic reviews (BioMed Central, 2012)
Systematic Reviews encompasses all aspects of the design, conduct and reporting of systematic reviews. The journal aims to publish high quality systematic review products including systematic review protocols, systematic reviews related to a very broad definition of health, rapid reviews, updates of already completed systematic reviews, and methods research related to the science of systematic reviews, such as decision modeling. The journal also aims to ensure that the results of all well-conducted systematic reviews are published, regardless of their outcome.